Radiographic film dosimetry of proton beams for depth‐dose constancy check and beam profile measurement. (8th May 2015) - Yeo, Inhwan J.; Teran, Anthony; Ghebremedhin, Abiel; Johnson, Matt; Patyal, Baldev
Abstract : Radiographic film dosimetry suffers from its energy dependence in proton dosimetry. This study sought to develop a method of measuring proton beams by the film and to evaluate film response to proton beams for the constancy check of depth dose (DD). It also evaluated the film for profile measurements. To achieve this goal, from DDs measured by film and ion chamber (IC), calibration factors (ratios of dose measured by IC to film responses) as a function of depth in a phantom were obtained. These factors imply variable slopes (with proton energy and depth) of linear characteristic curves that relate film response to dose. We derived a calibration method that enables utilization of the factors for acquisition of dose from film density measured at later dates by adapting to a potentially altered processor condition. To test this model, the characteristic curve was obtained by using EDR2 film and in‐phantom film dosimetry in parallel with a 149.65 MeV proton beam, using the method. An additional validation of the model was performed by concurrent film and IC measurement perpendicular to the beam at various depths. Beam profile measurements by the film were also evaluated at the center of beam modulation. In order to interpret and ascertain the film dosimetry, Monte Carlos simulation of the beam was performed, calculating the proton fluence spectrum along depths and off‐axis distances. By multiplying respective stopping powers to the spectrum, doses to film and water were calculated. The ratio of film dose to water dose was evaluated. Results are as follows. The characteristic curve proved the assumed linearity. The measured DD approached that of IC, but near the end of the spread‐out Bragg peak (SOBP), a spurious peak was observed due to the mismatch of distal edge between the calibration and measurement films. The width of SOBP and the proximal edge were both reproducible within a maximum of 5 mm; the distal edge was reproducible within 1 mm. At 5 cm depth, the dose was reproducible within 10%. These large discrepancies were identified to have been contributed by film processor uncertainty across a layer of film and the misalignment of film edge to the frontal phantom surface. The deviations could drop from 5 to 2 mm in SOBP and from 10% to 4.5% at 5 cm depth in a well‐controlled processor condition (i.e., warm up). In addition to the validation of the calibration method done by the DD measurements, the concurrent film and IC measurement independently validated the model by showing the constancy of depth‐dependent calibration factors. For profile measurement, the film showed good agreement with ion chamber measurement. In agreement with the experimental findings, computationally obtained ratio of film dose to water dose assisted understanding of the trend of the film response by revealing relatively large and small variances of the response for DD and beam profile measurements, respectively. Conclusions are as follows. For proton beams, radiographic film proved to offer accurate beam profile measurements. The adaptive calibration method proposed in this study was validated. Using the method, film dosimetry could offer reasonably accurate DD constancy checks, when provided with a well‐controlled processor condition. Although the processor warming up can promote a uniform processing across a single layer of the film, the processing remains as a challenge. PACS number: 87